Pika Gut May Select for Rare but Diverse Environmental Bacteria - Li, Huan; Li, Tongtong; Yao, Minjie; Li, Jiabao; Zhang, Shiheng; Wirth, Stephan; Cao, Weidong; Lin, Qiang; Li, Xiangzhen (Frontiers in Microbiology, 2016)
The composition of the mammalian gut bacterial communities can be influenced by the introduction of environmental bacteria in their respective habitats. However, there are no extensive studies examining the interactions between environmental bacteriome and gut bacteriome in wild mammals. Here, we explored the relationship between the gut bacterial communities of pika (Ochotona spp.) and the related environmental bacteria across host species and altitudinal sites using 16S rRNA gene sequencing. Plateau pikas (O. curzoniae) and Daurian pikas (O. daurica) were sampled at five different sites, and plant and soil samples were collected at each site as well. Our data indicated that Plateau pikas and Daurian pikas had distinct bacterial communities. The pika, plant and soil bacterial communities were also distinct. Very little overlap occurred in the pika core bacteria and the most abundant environmental bacteria. The shared OTUs between pikas and environments were present in the environment at relatively low abundance, whereas they were affiliated with diverse bacterial taxa. These results suggested that the pika gut may mainly selects for low-abundance but diverse environmental bacteria in a host species-specific manner.